Decision Support System for Determining Land Priority for Housing Development Using Fuzzy Analytical Process (Fuzzy-AHP) Method - Simarmata, Allwin M; Yennimar, Yennimar (Politeknik Ganesha Medan, 2019)
The National Housing Development Public Corporation (Perumnas) was established as a government solution in providing adequate housing for the middle to lower classes, to realize this, Perumnas set a target of building 100,000 houses / year. The aspect of development is to ensure that all communities occupy decent homes in a healthy environment, an increase in the number of residents in the city, especially the city of Medan, causes settlement problems because the area of land is a fixed factor, while the population is always growing, thus requiring a system that can help decision in determining the priority of land for housing development. In this study an analysis of patterns related to applicable criteria or rules is implemented by applying the Fuzzy Analytical Hierarchy Process (Fuzzy-AHP) method, to produce accurate and effective information for making priority decisions on the location of the best residential development land. The analysis framework uses a data collection approach sourced from Public Relations, then an analysis is carried out to determine the criteria, rules and standards used, then a system is built by implementing the Fuzzy-AHP method to produce optimal alternatives that can be used as information. Alternative results will be evaluated by quantitative and qualitative analysis compared to the existing system. The developed system is expected to be used as a tool in decision making in the Regional Sumatra Regional Public Corporation I company that is optimal according to the criteria, rules or standards used. Data collection using the method of literature study, observation, interviews, and sampling. This research is expected to be one of the references in the application of decision support systems in a real scope and contribute to building a constructive community culture based on logical and scientific values.